2022
DOI: 10.7759/cureus.30987
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the First-Pass Success Rate of the King LTS-D and the i-gel Airway Devices in Out-of-Hospital Cardiac Arrest

Abstract: Objectives: Significant heterogeneity exists internationally in the airway devices used in the pre-hospital setting during cardiac arrest. This study evaluated the first-pass success (FPS) rate of two supraglottic airways (SGAs) used by paramedics during out-of-hospital cardiac arrest: the King LTS-D and the i-gel. Methods: By examining 2,680 patient care records compiled by Ambulance New Brunswick between 2015 and 2020, we evaluated the FPS rate of the two SGAs using a 2x2 Pearson chi-square test for associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…retrospectively compared i‐gel ® to the King LT, with a higher (90.6% vs. 76.6%) first‐pass success rate. 18 In a randomized controlled prehospital airway trial from Australia, i‐gel ® was found to have a higher successful insertion rate (90%) in comparison to the first‐generation SGAs (57%). 19 In the AIRWAYS‐2 trial, 1523 paramedics randomized 9296 patients with OHCA to ETI versus the i‐gel ® SGA and found no significant differences in favorable functional outcome between ETI (6.8%) and i‐gel ® (6.4%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…retrospectively compared i‐gel ® to the King LT, with a higher (90.6% vs. 76.6%) first‐pass success rate. 18 In a randomized controlled prehospital airway trial from Australia, i‐gel ® was found to have a higher successful insertion rate (90%) in comparison to the first‐generation SGAs (57%). 19 In the AIRWAYS‐2 trial, 1523 paramedics randomized 9296 patients with OHCA to ETI versus the i‐gel ® SGA and found no significant differences in favorable functional outcome between ETI (6.8%) and i‐gel ® (6.4%).…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Price et al. retrospectively compared i‐gel ® to the King LT, with a higher (90.6% vs. 76.6%) first‐pass success rate 18 . In a randomized controlled prehospital airway trial from Australia, i‐gel ® was found to have a higher successful insertion rate (90%) in comparison to the first‐generation SGAs (57%) 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has a characteristic non-in atable cuff that can change its shape according to body temperature and provide a better t for individual patients after insertion [9,10]. Additionally, the standard i-gel® has a high rate of successful insertion on the rst attempt and a low incidence of blood stains caused by airway injury [11,12]. Therefore, it has been widely used in various situations, including laparoscopic surgery and prone positioning [13,14].…”
Section: Introductionmentioning
confidence: 99%